Electro-mechanical instability modelling in elastomeric actuators: A second law of thermodynamics-based approach. Issue 3 (3rd July 2019) - Kumar, Deepak; Sarangi, Somnath
ABSTRACT: In the present paper, we report an alternative method to model the electro-mechanical instability (EMI) phenomenon of the dielectric elastomeric (DE) actuators. The proposed method is based on a classical continuum mechanics approach followed by the second law of thermodynamics. We first formulate an electro-elastic deformation of a continua through an amended energy function followed by the theory of electro-elasticity. The amended energy function accounts the electrostriction phenomenon for a class of an incompressible isotropic electro-elastic material. In addition, the proposed energy function also overcomes the hurdle of the physical interpretation of the Maxwell stress tensor in large deformation. We then consider that the DE actuators are subjected to a pre-stretching effect through a simple loading with an applied electrical voltage across the thickness. Further, we develop the analytical EMI models for the DE actuators through a new amended energy function. Finally, the obtained EMI models through the proposed method are compared with an existing energy-based method, and also validated with the experimental data existing in the literature. The comparison and validation indicate that the proposed classical method is more realistic as compared to the existing one.